2021
DOI: 10.1016/j.euo.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Histological Subtype on the Incidence, Timing, and Patterns of Recurrence in Patients with Renal Cell Carcinoma After Surgery—Results from RECUR Consortium

Abstract: Background: Current follow-up strategies for patients with renal cell carcinoma (RCC) after curative surgery rely mainly on risk models and the treatment delivered, regardless of the histological subtype. Objective: To determine the impact of RCC histological subtype on recurrence and to examine the incidence, pattern, and timing of recurrences to improve follow-up recommendations. Design, setting, and participants: This study included consecutive patients treated surgically with curative intention (ie, radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
(54 reference statements)
4
25
0
Order By: Relevance
“…More specifically, 78% of ccRCC patients were disease free at 5 years versus 86% of pRCC and 91% of chRCC (p = 0.001). The association between histological subtype and recurrence rates remained statistically significant even in multivariable models taking into account the tumor stage, size, nuclear grade, vascular invasion, and surgical margin status [12]. It is of note that not only the recurrence rates were significantly different among different histological subtypes, but also the pattern of recurrence was significantly different.…”
Section: Tissue-based Biomarkersmentioning
confidence: 77%
See 4 more Smart Citations
“…More specifically, 78% of ccRCC patients were disease free at 5 years versus 86% of pRCC and 91% of chRCC (p = 0.001). The association between histological subtype and recurrence rates remained statistically significant even in multivariable models taking into account the tumor stage, size, nuclear grade, vascular invasion, and surgical margin status [12]. It is of note that not only the recurrence rates were significantly different among different histological subtypes, but also the pattern of recurrence was significantly different.…”
Section: Tissue-based Biomarkersmentioning
confidence: 77%
“…Histological subtype represents the most important feature to predict recurrence. In a recent analysis based on RECUR database, Abu-Ghanem et al showed that 5-year recurrence free survival rates significantly differ between ccRCC, papillary RCC (pRCC), and chromophobe RCC (chRCC) [12]. More specifically, 78% of ccRCC patients were disease free at 5 years versus 86% of pRCC and 91% of chRCC (p = 0.001).…”
Section: Tissue-based Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations